Answer:
Horizontal asymptote
![y=-(1)/(2)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/2fy7kxto2rkbhh3utveb67hq8qmv7ztf1i.png)
Explanation:
Given:
![y=(-3x^5+5x+4)/(6x^5+2x+5)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/ulzwf2444ho2wawa9ajbcd2fr6jnjthsx5.png)
We need to find horizontal asymptote
For horizontal asymptote, we check the degree of numerator and denominator
Degree of numerator = 5
Degree of denominator = 5
Here degree is same
Therefore, Horizontal asymptote, y= leading coefficient of numerator over leading coefficient of denominator
Leading coefficient of numerator = -3
Leading coefficient of denominator = 6
Horizontal asymtote:
![y=(-3)/(6)=-(1)/(2)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/btw5v9xtlqdz7qy6jfv2pbp5ujt6hg8ou0.png)
Hence, The horizontal asymptote is
![y=-(1)/(2)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/2fy7kxto2rkbhh3utveb67hq8qmv7ztf1i.png)